Profil Konsepsi IPA Siswa Kelas V di SDN Penjaringan Sari II - Nur Mazkiyah; Muhammad Thamrin Hidayat; Muslimin Ibrahim; Afib Rulyansah (Departement of Mathematics Education, 2023)
The conception profile is the distribution of students based on the conditions: Mastering the concept, Not mastering the concept, and experiencing misconceptions. While the profile of the science conception is a description of the students' conceptions of science learning in terms of science concepts. The purpose of this study was to determine the science conception profile of fifth grade students at SDN Penjaringan Sari II. Data collection techniques using observation, filling out tests and documentation. The data obtained was analyzed and then refined by grouping the degree of understanding of the concept and then calculating the percentage based on the decision making of the Three Tier Test. The results of this study indicate that the percentage of students in the category of not understanding the concept is higher than the category of understanding concepts and misconceptions. The low level of understanding of concepts possessed by students may be caused by 2 factors, namely students who do not understand the concept or students who experience misconceptions. The 5 factors that cause misconceptions in students according to Suparno (2013) include: Students, Teachers/Teachers, Textbooks, Context, Teaching methods